Experimental analysis of image encryption using elgamal and block-substitution method for color images. Issue 5 (4th July 2017) - Lokeshwari, G.; Udaya Kumar, S.; Susarla, Sreevidya
Abstract: This paper presents an encryption technique for color images. In this method byte code is extracted from the color image which is converted into binary data. Cipher text is generated by applying Block substitution encryption method on the obtained binary data. The effectiveness of the proposed method has been estimated by computing chi-square value. Obtained results show that the encryption method is suitable for both symmetric and asymmetric images of larger size.